Severe structural deterioration of small aortic bioprostheses treated with valve‐in‐valve transcatheter aortic valve implantation. Issue 1 (9th January 2019) - Stankowski, Tomasz; Aboul‐Hassan, Sleiman Sebastian; Seifi‐Zinab, Farzaneh; Herwig, Volker; Kubikova, Miroslava; Harnath, Axel; Fritzsche, Dirk; Perek, Bartłomiej
Abstract: Objectives: The aim of this study was to evaluate outcomes of valve‐in‐valve transcatheter aortic valve implantation (VIV‐TAVI) in patients with degenerated small bioprostheses. Methods: Outcomes of consecutive 27 high‐risk patients (logistic EuroSCORE 35.5 ± 18.5%) with a mean age of 81.0 ± 5.9 years who underwent VIV‐TAVI for degenerated small bioprostheses (19 mm‐11.1%; 20 mm‐11.1%; 21 mm‐77.8%) were analyzed. Medtronic CoreValve ( n  = 11) or CoreValve Evolut‐R prostheses ( n  = 16) were implanted. Follow‐up was 3.2 ± 2.0 years. Results: Early mortality was 11.1%. One patient died intraoperatively due to left ventricle perforation, two others during the in‐hospital period as a result of sudden cardiac death and pulmonary embolism. VIV‐TAVI was completed in 26 cases (96.3%—success rate). Two patients required pacemaker implantation. Acute kidney injury occurred in two other patients. At discharge, mean transvalvular gradient was 19.2 ± 9.5 mmHg and in 25.9% of patients mean gradient exceeded 20 mmHg. Overall mortality was 25.9% and mortality from cardiac or unknown causes at 18.5%. Ninety percent of survivors were in New York Heart Association (NYHA) class I or II. Conclusions: Transfemoral VIV‐TAVI in patients with small, degenerated bioprostheses appears to be a promising alternative to surgery. Although the vast majority of patients have significant improvement in their NYHA class, the rate of persistent, residual gradients is relatively high and will need to be followed closely with serial echocardiograms.